ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PRAKTIK PERATAAN LABA (Studi Pada Perusahaan Sektor Pertanian Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2017) - Rahel Marpaung, Apriliyanti; Kristanti, Farida Titik (Aksara Public, 2018)
Profit is one of the very important information in financial statements.Fluctuating earnings tend to show the high risk of the company. Income smoothing is one of the earnings management techniques carried out by management with the aim of reducing fluctuations in profits at a certain level in accordance with what is expected by the company. Income smoothing is measured using the Eckel Index (1981). This study aims to determine the effect of variables Net Profit Margin, Return On Assets, Debt to Equity Ratio, Debt to Asset Ratio on income smoothing practices.